2018
DOI: 10.1021/acs.chemmater.8b02871
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Oxygen Hybridization Determined Activity in Spinel-Based Oxygen Evolution Catalysts: A Case Study of ZnFe2–xCrxO4

Abstract: A good understanding of the correlation between electronic properties and catalytic performance is vital to the rational design of active oxygen evolution reaction (OER) catalysts. Here, a volcano-shaped correlation between the OER activity and the Cr substitution amount was found for spinel oxides ZnFe 2−x Cr x O 4 (x = 0−2), in which Zn 2+ resides in tetrahedral (Td) sites while Fe 3+ and Cr 3+ occupy octahedral (Oh) sites. Such a relationship probably is because Cr substitution tunes the e g occupancy of Oh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 57 publications
(154 reference statements)
1
51
0
Order By: Relevance
“…An anodic redox peak at about 1.43 V appeared in MgCo 2 O 4 , which was attributed to Co 3+ /Co 4+ couples (Figure a) . For CoCr 2 O 4 (Figure b), the first oxidation peak at about 1.10 V is corresponding to the oxidation of Co 2+ to Co 3+ and the second oxidation peak at about 1.30 V is attributed to Cr 3+ /Cr 4+ couples . The redox peak of Co 2+ /Co 3+ is at around 1.30 V (anodic) in Co 2 TiO 4 (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…An anodic redox peak at about 1.43 V appeared in MgCo 2 O 4 , which was attributed to Co 3+ /Co 4+ couples (Figure a) . For CoCr 2 O 4 (Figure b), the first oxidation peak at about 1.10 V is corresponding to the oxidation of Co 2+ to Co 3+ and the second oxidation peak at about 1.30 V is attributed to Cr 3+ /Cr 4+ couples . The redox peak of Co 2+ /Co 3+ is at around 1.30 V (anodic) in Co 2 TiO 4 (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…Positive correlation between the degree of Fe–O hybridization and OER performance has been built . It is worth noting that increased TM–O hybridization (defined as the percentage of O 2p states that hybridize with TM 3d states) is expected to give increased TM–O covalency . In different crystalline structures, the geometric tilting of FeO 6 octahedra alters the Fe−O−Fe bond angles and bond lengths, and therefore give Fe–O bond different hybridization degree.…”
Section: Metal–oxygen Covalency In Spinelmentioning
confidence: 89%
“…Further studies showed a strong correlation between OER activity and oxygen p‐band center relative to the Fermi level through theoretical calculations [26] . Other parameters, including cations in octahedral sites and transition metal 3d – O 2p hybridization, have been widely studied by metal doping or partial element substitution [27–30] . Surface reconstruction mediated by transition metals has been reported to form active reaction sites, such as oxyhydroxide sites on the catalyst interface [31,32] .…”
Section: Introductionmentioning
confidence: 99%